'1L=10L for Africa': Corporate social responsibility and the transformation of bottled water into a 'consumer activist' commodity. (January 2014) - Brei, Vinicius; Böhm, Steffen
In recent years, it has become an increasingly common marketing practice to connect the sale of consumer products to corporate social responsibility (CSR) initiatives, such as aid and development projects in so-called 'developing' countries. One example is Volvic's pioneering '1L=10L for Africa' campaign (2005–2010), which linked the sale of each liter of bottled water in 'developed' countries with the promise by Danone, Volvic's owner, to provide 10 liters of drinking water in Africa. In this article, we engage with this 'cause-related marketing' campaign, using critical discourse analysis (CDA) to uncover its mechanisms and ideological functioning. We show how Volvic was able to transform an ordinary commodity, bottled water, into a consumer activist brand through which consumers could take part in solving global social problems, such as the access to safe drinking water in 'developing' countries. Our analysis of this exemplary case shows the ways that CSR often operates to deflect ethical critiques, consolidate brand loyalty and corporate profits, and defuse political struggles around consumption. By doing so, we suggest that CSR forms part of a complex strategy deployed to legitimize particular brands and commodities. In this way CSR can be seen as playing an important role in the ideological makeup of contemporary consumer capitalism.